From environmental concerns to nationalist waves: Mapping the evolving Fukushima wastewater discourse on Weibo - Siwei Qin; WonJae Lee (PLoS ONE, 2026)
This study employed Structural Topic Modeling (STM) on 56,526 Weibo posts to examine the evolving discourses surrounding the Fukushima wastewater release. While rational discourse focusing on technical and environmental concerns initially coexisted and competed with nationalist narratives, the discourse rapidly transformed into predominantly nationalist rhetoric driven by grassroots users. Nationalism discourse was framed through two antagonisms: 1) direct, volatile anti-Japanese sentiment rooted in historical grievances and 2) broader, consistent anti-Western skepticism anchored in geopolitical rivalries. Moving beyond the binary paradigm of Chinese cyber-nationalism as either purely top-down mobilization or bottom-up explosion, this study reveals a nuanced interplay between actor types: grassroots users predominantly led nationalistic discourses, especially anti-Japanese discourse, while Key Opinion Leaders (KOLs) focused on technical discussions but occasionally amplified anti-Western sentiment. By identifying a latent nationalist sensitivity and a victimhood-centric view of international affairs, the study demonstrates how affective public sentiment can transform environmental issues into perceived insults to national dignity, intensified by platform-mediated grassroots agency.